Functional organization and dynamics of the cell nucleus - Guo, Tongtong; Fang, Yuda (Frontiers in Plant Science, 2014)
The highly ordered eukaryotic cell nucleus encapsulated by the nuclear envelope harbors the territorially organized chromatin and various nuclear bodies, and provides a relatively separate environment for replication, maintenance, transcription, and regulation of the genome. In this review, we focus on the four-dimensional organization of the nucleus including the nuclear envelope, chromatin, and nuclear bodies, and the dynamic processes related to the subnuclear compartments under various signals of development and stresses with a special focus on plant cell nuclei.